Depressive mood changes are associated with self-perceptions of ADHD characteristics in adults. (June 2021) - Ishizuka, Kanako; Ishiguro, Tomomi; Nomura, Norio; Inada, Toshiya
Highlights: Subjective symptoms of ADHD were enhanced by depressive states over time. Subjective ADHD symptoms were observed to be correlated with depressive states. Diagnosis of ADHD should be performed carefully in patients with depressive symptoms. Abstract: Subjective attention deficit/hyperactivity disorder (ADHD) symptoms seen in adult depressive patients have often become a pathophysiological topic in recent years. Screening questionnaires are widely used for detecting ADHD; however, the risk of misdiagnosis exists. The present study examined whether self-perceptions of ADHD-related characteristics were consistent regardless of changes in the severity of depressive symptoms. Between April to October 2018, newly diagnosed depressed outpatients aged 24–59 years with good social functioning and without a history of ADHD were asked to fill out the Adult ADHD Self-Report Scale version 1.1 (ASRS) and the Beck Depression Inventory (BDI) at baseline (n = 726) and 12-week follow-up (n = 202). A statistically significant correlation was found between a change in BDI and ASRS scores (score at baseline minus score at the endpoint; r = .57). In addition, the higher the rate of improvement in BDI, the lower the frequency of positive screening for ADHD by ASRS. This study showed that subjective ADHD symptoms were correlated with depressive states. Diagnostic evaluation of comorbid ADHD using self-report scales in a primary care setting should be made with caution.